Питание самцов и самок обыкновенного скворца в различные сезоны - Боярчук, В.П. (Вестник зоологии, 1981)
Essential differences are stated in feed composition of male and female Sturnus vul. garts L. in different seasons. It is supposed that these differences are not random, they are due to physiological causes, namely by sexual differences in demands of energy and plastic substances in different periods of life.